Experiences and needs of mothers of children with autistic disorder - Köktürk, Akşın Ceylan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
The purpose of this study was to understand mothers of children with autism in terms of their experiences, needs, difficulties, stress levels and supports. Thirty mothers whose children were diagnosed as autistic were interviewed individually. The children were between three to eight years old. Sixty percent of children were in the mild to moderate form of autism where fourty percent were severe. Semi-structured interviews were implemented to mothers to get detailed information about themselves and their children. Additionally, the Questionnaire on Resources and Stress (QRS-FT) was used to see mothers‟ sources of stress and the Family Support Scale (FSS) was used to see mothers‟ support systems. Mothers also completed family information forms. The results of interview analyses showed that there was a time interval between mothers‟ first recognition of a problem in their children and their application to a professional. They were mostly sad and shocked when they heard the word autism and some mothers still feel the same. The responsibility of children was mostly on the mothers. Most mothers did not have any free time to relax. Being mothers of autistic children effected the social lives of mothers negatively. Children‟s communication and behavioral problems were among the top difficulties that mothers had to cope with. Mothers mostly stated needs concerning their children, like schools that would accept their children, more therapy sessions and other therapies. To be well enough to lead independent lives was the shared future expectation for their children by mothers. Lastly, mothers expected other people to be more understanding, empathic and aware of autism. Results from quantitative data also showed that mothers of children with autism perceived middle levels of stress and support. Mothers tended to have the highest mean scores from the pessimisim factor and the lowest mean scores from the parent and family problems factor of QRS-FT. Mothers perceived emotional support the most and caregiving support the least.
Keywords: Autism in children.; Autistic children.; Parents of autistic children.